Identifying obstacles to the growth of new SMEs: A Factor Analysis Approach - Mphahlele, Dorothy B. (Identifying obstacles to the growth of new SMEs: A Factor Analysis Approach, 2019)
It is widely acknowledged that Small and Medium-Sized Enterprises (SMEs) are key drivers of economic growth and job creation in developing countries. It has also been established that new SMEs face common problems that arise as they grow and develop. These challenges stem from internal as well as external factors that can have an adverse impact on their survival and growth. The objective of this study was to identify the internal and external obstacles to the growth of SMEs. A questionnaire was used to collect data on factors affecting the growth of SMEs. The results of the questionnaire were analysed using Factor Analysis. Eight different factors were identified. These factors were further analysed to determine their impact on SMEs. The ranking of the factors in order of importance was as follows: lack of access to finance, overregulation, the economic environment, high competition, lack of internal resources, high input costs, lack of experience of the entrepreneur and poor service delivery. The report examines possible ways of mitigating the adverse factors identified and makes a series of recommendations to increase the likelihood of the survival of SMEs in the South African context.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Commerce University of the Witwatersrand, Johannesburg, 2019
Keywords: Small and Medium-Sized Enterprises (SMEs); Obstacles to growth; Environmental factors; Entrepreneurs; South Africa; UCTD; SDG-8: Decent work and economic growth